دور العدالة التنظيمية في بيان صوت العاملين (دراسة تحليلية لأراء عينة من العاملين في كليات جامعة صلاح الدين في مدينة أربيل) - القرداغي, كاوه محمد فرج; حسين, رازاو عبدالخالق (Sulaimani Journal for Humanities, 2022)
The aim of the research is to identify the role Organizational justice with its subdivisions (Distributive Justice, Procédural Justice, Ineractional Justice) in Employees Voice. The research presented theoretical and conceptual framework for the main and secondary variables. employes at the Colleges of SalahaddinUniversity and number of its directorates were chosen as a field for conducting the research. The importance of the research stems from the importance of the topics examined. The research was systematically and descriptively analyzed, and a set of hypotheses was identified as probative responses to the research problem, which were tested using multiple statistical tools, using the SPSS-V.20 statistical program. The questionnaire was used as a means of obtaining the data. It was distributed to a sample of employes of Salahaddin University The number of employe was 85, and 80 questionnaires were retrieved and all were valid for analysis. The study concluded that there is a relationship and influence for all dimensions of Organizational justice in Employees Voice. The research recommended employing this relationship to serve the employe of Colleges SalahaddinUniversity.
Keywords: Organizational justice; Distributive Justice; Procédural Justice; Ineractional Justice; Employees Voice; Supportive Voice; Obstructive Voice